Fine Structure of Bacteroids in Root Nodules of Vigna sinensis, Acacia longifolia, Viminaria juncea, and Lupinus angustifolius - Dart, P. J. (1966)
Dart, P. J. (University of Sydney, Sydney, Australia), and F. V. Mercer. Fine structure of bacteroids in root nodules of Vigna sinensis, Acacia longifolia, Viminaria juncea, and Lupinus angustifolius. J. Bacteriol. 91:1314–1319.—In nodules of Vigna sinensis, Acacia longifolia, and Viminaria juncea, membrane envelopes enclose groups of bacteroids. The bacteroids often contain inclusion granules and electron-dense bodies, expand little during development, and retain their rod form with a compact, central nucleoid area. The membrane envelope may persist around bacteroids after host cytoplasm breakdown. In nodules of Lupinus angustifolius, the membrane envelopes enclose only one or two bacteroids, which expand noticeably during development and change from their initial rod structure.